2000
DOI: 10.1021/es990768n
|View full text |Cite
|
Sign up to set email alerts
|

Video Display Units:  An Emission Source of the Contact Allergenic Flame Retardant Triphenyl Phosphate in the Indoor Environment

Abstract: Triphenyl phosphate, an additive flame retardant with documented contact allergenic effects on humans, was identified in a computerized indoor office environment. The source of emission was found to be the computer video display units (VDUs). Eighteen VDUs were examined, and the outer covers were shown to contain triphenyl phosphate in levels up to 10% (w/w). When using this type of PC equipment with a brand-new VDU in a small office room, the air concentration of triphenyl phosphate raised to near 100 ng/ m 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 17 publications
1
70
1
Order By: Relevance
“…These findings confirm the influence of the e-waste recycling activities on the BJ River. TPhP is used on a large scale in developed countries as a plasticizer and flame retardant in a variety of electronic equipment (Carlsson et al, 2000). As TPhP is added to but not bonded with the materials, it is readily released from the e-waste products to the environment.…”
Section: Patterns and Compositional Analysismentioning
confidence: 99%
“…These findings confirm the influence of the e-waste recycling activities on the BJ River. TPhP is used on a large scale in developed countries as a plasticizer and flame retardant in a variety of electronic equipment (Carlsson et al, 2000). As TPhP is added to but not bonded with the materials, it is readily released from the e-waste products to the environment.…”
Section: Patterns and Compositional Analysismentioning
confidence: 99%
“…VOCs identified in the emissions from printing and copying devices include chemicals listed on the State of California's Toxic Air Contaminants (TACs) list (OEHHA, 2000), such as benzene, toluene, ethylbenzene, xylenes, and styrene, formaldehyde and acetaldehyde (Lee et al, 2001; Leovic et al, 1996;Leovic et al, 1998). The plastic covers of video-display units (VDUs) have been shown to contain and emit triphenylphosphate and other organophosphate esters used as flame retardants (Carlsson et al 2000). Electronic devices including office equipment contain and emit a number of brominated flame retardants such as the polybrominated diphenyl ethers (PBDEs), among other identified semivolatile organic compounds (SVOCs).…”
Section: Overview Of Existing Studiesmentioning
confidence: 99%
“…Ozone emissions from office equipment have been studied in the context of understanding indoor ozone exposures (Wolkoff 1999). Inhalation exposure to toner dust has been implicated in case reports as causing respiratory impairment (Gallardo et al 1994;Armbruster et al 1996 Carlsson et al, 2000). PBDEs, which are classified as endocrine-disrupting compounds (Rudel et al 2003), have been shown to accumulate in human breast milk (Noren and Meironyte 2000).…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…TPHP concentration was higher upper surface dust than floor dust. These results implicated that the dominant source of TPHP might be on or near upper surface dust, such as consumer products, furniture, and electric devices (Carlsson et al, 2000;Marklund et al, 2005;Sabine Kemmlein, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…TPHP and TCEP are emitted from televisions and computers (Carlsson et al, 2000;Hartmann et al, 2004;Saito et al, 2007). 3.7. Comparison of the results of this study with those of previous studies Table 6 shows the concentrations of PFRs in this study compared with those in previous studies of private homes because PFR concentrations can vary depending on the sampling site (Bergh et al, 2011;Van den Eede et al, 2011).…”
Section: Comparison Of Floor Dust Between 2009 and 2010mentioning
confidence: 99%